Congenital esophageal stenosis owing to tracheobronchial remnants - Rebelo,Priscila Guyt (2013)
OBJECTIVE To emphasize the need of an accurate diagnosis of congenital esophageal stenosis due to tracheobronchial remnants, since its treatment differs from other types of congenital narrowing. CASE DESCRIPTION Four cases of lower congenital esophageal stenosis due to tracheobronchial remnants, whose definitive diagnosis was made by histopathology. Except for the last case, in which a concomitant anti-reflux surgery was not performed, all had a favorable outcome after resection and anastomosis of the esophagus. COMMENTS The congenital esophageal stenosis is an intrinsic narrowing of the organâ€(tm)s wall associated with its structural malformation. The condition can be caused by tracheobronchial remnants, fibromuscular stenosis or membranous diaphragm and the first symptom is dysphagia after the introduction of solid food in the diet. The first-choice treatment to tracheobronchial remnants cases is the surgical resection and end-to-end anastomosis of the esophagus.